SISTEM MUNASAKHAH DALAM KEWARISAN - Rukiah Rukiah (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2014)
This article describes the problem Munasakhah system in the division of property in the Islamic inheritance. Discussion of the results obtained by the understanding that the settlement system munasakhah in inheritance cases should have the elements and forms munasakhah. The occurrence of cases munasakhah due to the death twice in the heirs will receive an inheritance from the heir before the property was divided on the first death of the testator. The advantage of this system is the part munasakhah second heir, the original heir blocked (Mahjub hirman).